Fibrinogen‐derived fibrinostatin inhibits tumor growth through anti‐angiogenesis. Issue 11 (16th October 2015) - Zhao, Chuanke; Su, Yahui; Zhang, Jianzhi; Feng, Qin; Qu, Like; Wang, Lixin; Liu, Caiyun; Jiang, Beihai; Meng, Lin; Shou, Chengchao
Abstract : Angiogenesis is a prerequisite of tumor growth and metastasis and, thus, anti‐angiogenesis treatment has become an important part of cancer therapy. A 15‐amino acid peptide of the fibrinogen α chain, fibrinostatin, was previously found in serum samples of gastric cancer patients. Herein we demonstrated that fibrinostatin has anti‐angiogenesis activity in several angiogenesis models and it reduces tumor growth in mouse xenografts and allografts. Increased tumor necrosis and reduced microvessel density in tumors were observed in mouse xenograft models. Fibrinostatin inhibited proliferation and induced apoptosis in HUVEC, but not in cancer cells. In addition, fibrinostatin specifically entered HUVEC. Fibrinostatin also prevented migration, adhesion and tubule formation of HUVEC in vitro . A single‐dose acute toxicity testing and a repeated‐dose chronic toxicity study in the mouse, rat and monkey indicated that fibrinostatin had a wide margin of safety. Taken together, fibrinostatin shows promise as a potential anti‐angiogenesis therapeutic agent. Abstract : This study reports that a 15‐amino acid peptide of the amino terminus of the fibrinogen α chain, fibrinostatin, inhibis tumor growth through its anti‐angiogenesis effect. The wide margin of its safety shows promise as a potential anti‐angiogenesis therapeutic agent.